Don’t blame women for low libido. Sexual sparks fly when partners do their share of chores – including calling the plumber - Buzwell, Simone; Johansen, Eva (The Conversation, 2022)
When a comic about “mental load” went viral in 2017, it sparked conversations about the invisible workload women carry. Even when women are in paid employment, they remember their mother-in-law’s birthday, know what’s in the pantry and organise the plumber. This mental load often goes unnoticed. Women also continue to do more housework and childcare than their male partners. This burden has been exacerbated over the recent pandemic (homeschooling anyone?), leaving women feeling exhausted, anxious and resentful. As sexuality researchers, we wondered, with all this extra work, do women have any energy left for sex?
Keywords: 2000 à aujourd'hui; 2020-2029; australie; charge mentale; discipline; désir; océanie; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sexologie; sexualité; thématiques

Orchids, intersex and the auto/biographical project - Hart, Phoebe (Studies in Documentary Film, 2013)
Auto/biographical documentaries ask audiences to take a ‘leap of faith’, not being able to offer any real 'proof of the people and events they claim to document, other than that of the film-maker's saying this is what happened. With only memory and history seen through the distorting lens of time, ‘the authenticity of experience functions as a receding horizon of truth in which memory and testimony are articulated as modes of salvage’. Orchids: My Intersex Adventure follows a salvaging of the film-maker's life events and experiences, being born with an intersex condition, and, via the filming and editing process, revolving around the core question: who am I? From this transformative creative documentary practice evolves a new way of embodying experience and ‘seeing’, playfully dubbed here as the ‘intersex gaze’.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; approches et analyses; australie; autoethnographie; cinéma; cinéma documentaire; communication; corps; cours; discipline; discours dominant; identités; intersexuation; inégalités; océanie; premier cycle; périodes historiques; régions géographiques; sexualité; soc2014; systèmes d'oppressions; thématiques; violences; violences médicales

Transcultural bodies: female genital cutting in global context - Hernlund, Ylva; Shell-Duncan, Bettina (Rutgers University Press, 2007)
Female "circumcision" or, more precisely, female genital cutting (FGC), remains an important cultural practice in many African countries, often serving as a coming-of-age ritual. It is also a practice that has generated international dispute and continues to be at the center of debates over women's rights, the limits of cultural pluralism, the balance of power between local cultures, international human rights, and feminist activism. In our increasingly globalized world, these practices have also begun immigrating to other nations, where transnational complexities vex debates about how to resolve the issue. Bringing together thirteen essays,Transcultural Bodiesprovides an ethnographically rich exploration of FGC among African diasporas in the United Kingdom, Europe, and Australia. Contributors analyze changes in ideologies of gender and sexuality in immigrant communities, the frequent marginalization of African women's voices in debates over FGC, and controversies over legislation restricting the practice in immigrant populations.
Keywords: afrique; anthropologie; approches et analyses; australie; corps; cours; discipline; europe; histoire et politique; océanie; premier cycle; racisme; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sex2283; sexisme; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; transculturalisme; violences

Chapitre XVII Sexe Et Tempérament et Conclusion dans Moeurs et sexualité en Océanie: au coeur des sociétés traditionnelles des îles Samoa et de Nouvelle-Guinée - Mead, Margaret; Chevassus, Georges (Moeurs et sexualité en Océanie: au coeur des sociétés traditionnelles des îles Samoa et de Nouvelle-Guinée, 1963)
Dans le texte Adolescence à Samoa (1928), l'auteure soutient que l'adolescence n'est pas une étape nécessaire entre l'enfance et l'âge adulte. Dans le texte Trois sociétés primitives de Nouvelle-Guinée (1935), elle analyse, à partir de ses observations de terrain, les différences de caractère entre hommes et femmes.
Keywords: anthropologie; approches et analyses; corps; cours; discipline; océanie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; soc3113; sociologie; système colonial; systèmes d'oppressions; thématiques